State of the Art in Crystallization of LiNbO3 and Their Applications - Kunfeng Chen (MDPI AG, 2021)
Lithium niobate (LiNbO3) crystals are important dielectric and ferroelectric materials, which are widely used in acoustics, optic, and optoelectrical devices. The physical and chemical properties of LiNbO3 are dependent on microstructures, defects, compositions, and dimensions. In this review, we first discussed the crystal and defect structures of LiNbO3, then the crystallization of LiNbO3 single crystal, and the measuring methods of Li content were introduced to reveal reason of growing congruent LiNbO3 and variable Li/Nb ratios. Afterwards, this review provides a summary about traditional and non-traditional applications of LiNbO3 crystals. The development of rare earth doped LiNbO3 used in illumination, and fluorescence temperature sensing was reviewed. In addition to radio-frequency applications, surface acoustic wave devices applied in high temperature sensor and solid-state physics were discussed. Thanks to its properties of spontaneous ferroelectric polarization, and high chemical stability, LiNbO3 crystals showed enhanced performances in photoelectric detection, electrocatalysis, and battery. Furthermore, domain engineering, memristors, sensors, and harvesters with the use of LiNbO3 crystals were formulated. The review is concluded with an outlook of challenges and potential payoff for finding novel LiNbO3 applications.